Surveying of Perspectives on Teaching Piano Online at Shenyang Conservatory of Music - Pan Lu; Pramote Danpradit (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
The purpose of this paper is to explore the feasibility of setting up an online piano education program at the Shenyang Conservatory of Music. The researcher developed the survey according to the advice of experts and surveyed five issues: The researchers used the survey to find confidence and online surveyed 80 piano teachers from November to December 2021 at the Shenyang Conservatory of Music. The results of the research were as follows: the survey respondents were 80 piano teachers, and 95% were interested or agreed to teach online. There are 95% of people who think computers are very useful and powerful, and using mobile phones is more convenient and smaller to meet their needs and can substitute piano lessons by 70%. There are 55% of people who think it's the same as the tradition, just on a different platform. There are 67.50% of people who think it's online, but it's actually closer to the students. There are 41.25% of people who think the school will have more students because it is more modern and keeps pace with the times. There are understanding the online by 95% of people fully agree with the online piano course model, and 65% of the people in the survey agree with the use of a telephone for online teaching and find its convenience.